ULRTASTRUCTURE OF MYOCARDIUM BLOOD ENDOTHELIAL CELLS IN DYNAMICS OF RATS’ AGING ON BACKGROUND OF APPLICATION OF CRYOPRESERVED CORD BLOOD PREPERATION - Мартинова, Ю.В.; Nevzorov, V.P.; Babiychuk, V.G.; Chernyavskaya, E.A.; Kulik, V.V. (World of Medicine and Biology, 2015)
There were performed electron microscopy studies of rat myocardium’s endothelial capillaries in the dynamics of aging on the background of the frozen-thawed cord blood nucleated cells preparation containing hematopoietic stem cells. A typical structure of endotheliocytes was shown to be kept in the 6 and 12 months old animals, while in the 18 and 24 months old rats a sharp increase in the number of micropinocytic vesicles, ribosomes and polysomes took place. There was observed an activation of the metabolic and synthetic activity of the endothelial cells of aging rats. The results of this work can be used for comparison with the rates of biochemical, electrophysiological and other studies in order to create the overall picture of the myocardium’s changes during aging on the background of application of cord blood stem cells.
Keywords: cord blood nucleated cells; mitochondria; endothelial cells; rats